Psychological well-being in primary survivors of Uttarakhand disaster in India - Srikant Sharma (Indian Journal of Social Psychiatry, 2015)
Introduction: After the 2004 Tsunami, India faced the worst natural disaster in Uttarakhand causing devastating floods and landslides. Besides the material harm, the disaster also has a massive impact on individual′s mental health, and the impact is perceived more in developing countries due to being densely populated with limited resources. The current study is an attempt to evaluate the psychological impact and its risk factors in Uttarakhand disaster. Methods: This cross-sectional study was conducted after 1 month of disaster in the primary survivors. All the included subjects were administered the semi-structured proforma for assessing the sociodemographic profile and the assessment instruments: Impact of events scale-revised (IES-R), depression anxiety stress scale and life orientation test-revised (LOT-R). Data were imputed and analyzed using Statistical Package for Social Sciences version 17.0.1 (SPSS Inc., Chicago, IL, USA). Results: About 58% subjects had posttraumatic stress disorder and significantly severe levels of depression, anxiety, and stress were noted in 45.3%, 57%, and 44.2% subjects, respectively. A physical illness was present in 36% subjects. Loss of at least one family member was reported by 12.8% subjects. LOT-R scores were negatively correlated to IES-R. Conclusion: Psychological morbidity in the immediate post-disaster period is high. Higher levels of depression, anxiety and stress with development of negative outlook regarding their future is observed with increasing age. Increasing age, lower educational levels, physical illness, loss of a family member, and pessimistic expectations were associated with adverse psychological sequelae.